TNFRSF13B/TACI Alterations in Turkish Patients with Common Variable Immunodeficiency and IgA Deficiency - Karaca, Neslihan Edeer (Avicenna J Med Biotechnol, 2018)
BACKGROUND: The Transmembrane Activator and Calcium modulator ligand Interactor (TACI), encoded by TNFRSF13B/TACI gene, is mutated in some patients with Common Variable Immunodeficiency (CVID) and IgA Deficiency (IgAD). The purpose of the study was to investigate for the first time in Turkish patients the prevalence of TNFRSF13B alterations in CVID, selective and partial IgAD patients. METHODS: Forty two CVID, 36 selective IgAD, 34 partial IgAD and 25 healthy controls were included. All patients were examined for TNFRSF13B gene mutations by PCR. RESULTS: The percentages of TNFRSF13B mutations in CVID, selective and partial IgAD patients were 7.1, 2.7 and 2.9%, respectively. No disease causing TNFRSF13B mutation in healthy controls was found. Patients with TACI mutations had recurrent respiratory tract infections. None of them experienced autoimmunity, bronchiectasis or granulomatous disease. In conclusion, TNFRSF13B mutations were present not only in CVID patients, but also in IgAD cases. CONCLUSION: Modifier genes as well as their combination with other genetic or environmental factors may play an important role in the development of the immunodeficiency phenotype.